2002
DOI: 10.1002/art.10113
|View full text |Cite
|
Sign up to set email alerts
|

Angiostatin gene transfer as an effective treatment strategy in murine collagen‐induced arthritis

Abstract: Objective. To determine the efficacy of local therapy with human angiostatin gene in murine collageninduced arthritis (CIA).Methods. DBA/1 mice were immunized with bovine type II collagen. Before the onset of arthritis, NIH3T3 fibroblasts, transduced with angiostatinexpressing retroviral vectors or control vectors, were transplanted into the knee cavity. The incidence of arthritis in the knee joints was evaluated histologically based on pannus formation and cartilage destruction. Paws were evaluated macroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 29 publications
0
45
0
1
Order By: Relevance
“…[22][23][24][25][26] Moreover, retrovirally delivered angiostatin also reduced pannus formation and neovascularization. 27 Other studies have reported that endostatin, a 20 kDa fragment of collagen XVIII, can also reduce disease. Intrasynovial injection of human recombinant endostatin reduced both the volume of grafted synovium and the number of vessels in SCID mice engrafted with human RA synovium.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] Moreover, retrovirally delivered angiostatin also reduced pannus formation and neovascularization. 27 Other studies have reported that endostatin, a 20 kDa fragment of collagen XVIII, can also reduce disease. Intrasynovial injection of human recombinant endostatin reduced both the volume of grafted synovium and the number of vessels in SCID mice engrafted with human RA synovium.…”
Section: Discussionmentioning
confidence: 99%
“…41 On day 21, the animals were boosted with an intradermal injection of 100 mg type II collagen emulsified in Freund's incomplete adjuvant (GIBCO BRL, NY, USA). Gradual onset of arthritis normally starts approximately 4 weeks after initial immunization.…”
Section: Methodsmentioning
confidence: 99%
“…43 On day 21, the animals were boosted with an intradermal injection of 100 mg type II collagen emulsified in Freund's incomplete adjuvant (GIBCO BRL, NY, USA). At 2 days after the boosting, the mice were divided into two groups and individually treated with either 15 mg of plasmid DNA containing cDNA for sTNFR:Fc or control plasmid.…”
Section: Intramuscular Dna Injection and Electroporationmentioning
confidence: 99%
“…Levels of vWF were expressed as a percentage, in which the detected vWF was compared with that present in a human plasma calibration standard arbitrarily assigned a value of 100%. 43 The levels of cytokines were normalized to the total amount of protein prepared from tissue lysates, as measured by way of a DC protein assay kit (Bio-Rad Laboratories, Hercules, CA, USA).…”
Section: Histologic Processing and Analysis Of Knee Jointsmentioning
confidence: 99%